Effect of replacing soybean meal with urea or encapsulated nitrate with or without elemental sulfur on nitrogen digestion and methane emissions in feedlot cattle - Rebelo, Lucas R. [UNESP]; Luna, Irene C.; Messana, Juliana D. [UNESP]; Araujo, Rafael C.; Simioni, Tiago A. [UNESP]; Granja-Salcedo, Yury T. [UNESP]; Vito, Elias S. [UNESP]; Lee, Chanhee; Teixeira, Izabelle A.M.A. [UNESP]; Rooke, John A.; Berchielli, Telma T. [UNESP] (Elsevier, 2019)
The objective of this study was to investigate the replacement of a true protein source (soybean meal, SBM) with non-protein nitrogen (NPN) sources (urea, U; or encapsulated nitrate (NO3 −), EN) and corn with or without the addition of elemental sulfur (S0) to the NPN diets on digestibility, nitrogen metabolism, microbial protein synthesis (MPS) efficiency, and methane (CH4) emissions in growing beef cattle. Ten ruminally-cannulated steers were used in a replicated 5 × 5 Latin square design (five pure-bred Nellore and five cross-bred Angus × Nellore) with 5 periods of 21 d each (14 d for diet adaptation and 7 d for sample collection). The total mixed ration contained chopped Tifton 85 hay as a forage source in a 50:50 (wt/wt) concentrate to forage ratio (DM basis). The treatments were: SBM as control; U; U plus S0 (US); EN; and EN plus S0 (ENS). Inclusion level of EN was 20 g/kg DM (equivalent to 14.3 g NO3 −/kg DM). Urea inclusion (8 g/kg DM) was calculated to supply the same amount of NPN as the EN diets. Elemental sulfur was included at 2.4 g/kg DM. Animals fed NPN diets (U or EN) had lower (P ≤ 0.01) DMI, OMI, and aNDFI compared to animals fed SBM. Animals fed EN consumed less (P = 0.006) N than animals fed U-containing diets. Nitrogen excreted in feces and urine was lower (P ≤ 0.05) for animals fed NPN diets compared to SBM, but N digestibility did not differ (P = 0.30) between diets. Rumen pH was greater (P < 0.001) for EN compared to U diets. Animals fed NPN diets had lower (P = 0.03) daily CH4 emissions compared to SBM (76.5 vs. 95 g CH4/d, respectively). Addition of S0 to NPN-containing diets did not alter (P ≥ 0.06) any parameter evaluated. Encapsulated nitrate and corn with or without the addition of elemental sulfur partially replacing SBM or as an alternative source of NPN to urea in beef cattle diets did not decrease CH4 emissions or adversely affect microbial protein synthesis.
Keywords: Beef cattle; Encapsulated nitrate; Methane; Microbial protein synthesis; Non-protein nitrogen